Impact of the WTO Agreement on MENA Agriculture - Chaherli, Nabil; El-Said, Moataz (2000)
The paper reviews the status of MENA agriculture trade and policies in relation with the Uruguay Round Agreement on Agriculture and future WTO negotiations. Using country-specific economy-wide models, the paper quantifies the impact of unilateral trade liberalization and reduction in domestic policy distortions. Drawing on these results and the current status of MENA agriculture, the paper provides recommendations in designing domestic policies to mitigate the likely unfavorable income redistribution effects in the context of the new trading system and increased localization. It also analyzes policy options that would contribute most to the expansion of developing country exports; and how the WTO process can be used to improve domestic policies to support MENA's rural economies."--Abstract.